A densidade energética como medida em peixes parasitados sob a luz da Teoria da Rainha Vermelha. - Pera, Carolina Costa (2014)
The way energy is optimized in different demands among vital periods of organisms has deep effects on its function. As posited in Red Queen Theory, the energy control and distribution, provided by the environment, is due to the population?s success in its opposite biotic relations. This work is original for assessing the route of the energetic density in affected and unaffected fishes in two lakes isolated from the Upper Paraná River floodplain plains in rainy seasons during three year consecutively. The investigation analyzed, throughout anova hierarchical, if there were expressive differences in the energetic content of muscles and gonads; the analysis of dissimilarities among places was conducted using Spearman correlation, a non-parametric method. Despite the high parasite prevalence, there were differences in organs only in sampling locations. The parasitism effect was not noticed when the analysis were made in each lake separately, which demonstrates environmental heterogeneity of the upper Paraná Tiver flooding plains. It can be concluded that the environmental influences were determining for the relevant differences among energetic density of muscles and gonads being more effective than parasitism. The permanence of Energetic Ecology and Parasitism relation is encouraged concerning the fast coevolution, in order to improve the knowledge about natural population's failure and success.